Perbandingan Product Layout dan Process Layout dalam Perbaikan Tata Letak PT. Almicos Pratama dengan Metode Simulasi - Hendry Sugianto Setiawan; Tanti Octavia; Stanley Surya Jaya (Jurnal Titra, 2016)
Competition in the industrial world forcing every company to have a strategy in their production process. Layout arrangement is one of the strategy that can be done so that the production process can run more efficiently. Two strategies that can be used in the layout arrangement are product layout and process layout. The initial layout, product layout, and process layout will be simulated by using Promodel software. Research in this final project will determine the best layout through the comparison of the four factors which are output of products, transportation time, operator utility, and moment. These results indicate that the process layout is better when compared with the initial layout and product layout of the four factors above. Comparison with the initial layout show that the product output from process layout can be increased by 37.49% for can product and 55.22% for lid product. Average transport time on the process layout can be decreased by 88.97%. The average operator utility on the process layout can be increased by 41.81%. Moment of the process layout can be decreased by 53.80%.